Gender and Language: A Review of Theoretical and Empirical Insights - Mishra, Priyanka (Journal of Advanced Research in English & Education; Vol 9 No 3 (2024): Journal of Advanced Research in English & Education, 2024)
Gender and language are deeply interconnected, shaping how individuals communicate and construct social identities within various social contexts. This review explores the theoretical frameworks and empirical research that examine the complex relationship between gender and language. Key concepts such as gendered language use, gender performance, and language in different social contexts are central to understanding how language both reflects and reinforces gender inequalities. The review highlights how language operates as a powerful tool for the expression of gender identity, power dynamics, and social norms. Furthermore, the article examines how language is influenced by societal attitudes toward gender, providing insights into the ways in which linguistic practices contribute to the perpetuation or disruption of gender norms. By synthesizing insights from both theoretical and empirical studies, this article provides a comprehensive understanding of how language both reflects and reinforces gender inequalities, while also offering avenues for promoting inclusivity, diversity, and social change. Through a critical analysis of contemporary research, the review identifies key areas for future investigation, including intersectionality, digital communication, and the role of media in shaping gendered language use. Additionally, the review underscores the importance of addressing biases and stereotypes embedded in language, as well as the potential for linguistic interventions to challenge discriminatory practices. The intersection of language with power relations, social justice, and cultural transformation continues to be a rich area of exploration, requiring ongoing scholarly attention. Through this review, readers are invited to engage with the evolving discussions around how language functions as a site of both reinforcement and resistance to gendered social structures.